2021
DOI: 10.1101/2021.08.13.21262006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered increase in STAT1 expression and phosphorylation in severe COVID-19

Abstract: The interferon pathway represents a key antiviral defense mechanism and is being considered as a therapeutic target in COVID-19. Both, substitution of interferon and blocking interferon signaling through JAK STAT inhibition to limit cytokine storms have been proposed. However, little is known so far about possible abnormalities in STAT signaling in immune cells during SARS-CoV-2 infection. In the current study, we investigated downstream targets of interferon signaling, including STAT1, pSTAT1 and 2 and IRF1, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Recently, investigators found that alterations in the immune response of individuals with severe SARS-CoV-2 infection are similar to those associated with autoimmunity, leading to new insights into immunopathogenesis. For example, COVID-19 and SLE both involve increased induction of extrafollicular CD19 high CD11c high B cells (26,43), as well as changes in the interferon response (44,45) and its regulation (46). Associations between COVID-19 and new-onset autoimmune rheumatic diseases, including SLE, were recently described (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, investigators found that alterations in the immune response of individuals with severe SARS-CoV-2 infection are similar to those associated with autoimmunity, leading to new insights into immunopathogenesis. For example, COVID-19 and SLE both involve increased induction of extrafollicular CD19 high CD11c high B cells (26,43), as well as changes in the interferon response (44,45) and its regulation (46). Associations between COVID-19 and new-onset autoimmune rheumatic diseases, including SLE, were recently described (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Although not shown in respiratory viral infection, several studies, found the sialic acid containing monosialodihexosylganglioside (GM3) to be another physiological ligand of CD169 (54)(55)(56)(57) In vivo analyses revealed a direct and clear upregulation of the receptor upon IFN-I (α/β/ω) stimulation within the physiological ranges of viral infection (58). In addition, significant changes in pSTAT1 and pSTAT2, pathways that are crucially involved in antiviral activity, have been detected (58,59). Of note, CD169+ macrophages have been found to be one of the main IFN-1 producers upon virus infection, themselves, making a selfenforcing process of IFN-mediated antiviral activity conceivable (27).…”
Section: Mechanisms Of Induction and Cell Population Maintenancementioning
confidence: 99%
“…Regarding the STAT pathway, another important regulatory relationship, it is particularly important that the JAK/STAT (Janus kinase/ Signal Transducer and Activator of Transcription) pathway regulates inflammatory cytokine signaling associated with SARS-CoV-2 infection. In monocytes, STAT1, STAT2 and IFN regulatory factors are activated [59,60]. The above hypothesized mechanisms provide us with a new perspective on MACROH2A1-mediated severe COVID-19 pathogenesis, and further in vitro and in vivo studies are warranted.…”
Section: Discussionmentioning
confidence: 91%